Highly light-tunable memristors in solution-processed 2D materials/metal composites - Sheykhifar, Zahra; Mohseni, Seyed Majid (Scientific reports, 2022)
Memristors—competitive microelectronic elements which bring together the electronic sensing and memory effects—potentially are able to respond against physical and chemical effects that influence their sensing capability and memory behavior. However, this young topic is still under debate and needs further attention to be highly responding to or remaining intact against physical effects, e.g., light illumination. To contribute to this scenario, using a composite of two-dimensional graphene or MoS 2 doped with meso-structures of metal/metal-oxides of Ag, Cu and Fe family, we presented scalable and printable memristors. The memristive behavior shows strong dependency upon light illumination with a high record of 10 5 ON/OFF ratio observed so far in 2-terminal systems based on two-dimensional materials or metal oxide structures. Moreover, we found that the memristors can remain stable without illumination, providing a novel approach to use these composites for developing neuromorphic computing circuits. The sensing and memristive mechanisms are explained based on the electronic properties of the materials. Our introduced materials used in the memristor devices can open new routes to achieve high sensing capability and improve memristance of the future microelectronic elements.